RESPONS KARAKTER FISIOLOGI TANAMAN KEDELAI (Glycine max L.) TERHADAP GENANGAN DAN PEMBERIAN PUPUK NITROGEN - Rusmana Rusmana; Sri Ritawati; Eltis Panca Ningsih; Alfianurtasya Alfianurtasya (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2021)
This research was aimed to know effect of Physiological Character Response of Soybean Plants (Glycine max L.) on Waterlogging and Nitrogen Fertilizer. This research has been conducted from November 2019 until January 2020 at Green House Faculty of Agriculture, Sultan Ageng Tirtayasa University, Serang, Banten. This research used a Randomized Block Design with two factors, the first factor was waterlogging of four levels: 100% Soil Water Available (SWA), 125% SWA, 150% SWA, 175% SWA. The second factor was nitrogen fertilizer of three levels: 0 kg ha-1), 25 kg ha-1), 50 kg ha-1 with three replication. The results showed that treatment of waterlogging affects the number of soybean plant leaves at five Weeks After Planting (WAP). The number of leaves in the waterlogging treatment is 175% less compared to the waterlogging of 100% SWA, 125% SWA, and 150% SWA. Nitrogen treatment affects the stomata length of soybean crops. Nitrogen fertilizer doses of 50 kg ha-1 have a lower stomata length compared to doses of 0 kg ha-1 and 25 kg ha-1. There is interaction in the treatment of waterlogging and nitrogen fertilizers at a plant height of 2 WAP.